2015
DOI: 10.1200/jco.2015.33.3_suppl.15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel upregulated microRNAs in the pathogenesis of gastric cancer by the use of open access databases and bioinformatics tools.

Abstract: 15 Background: Gastric cancer (GC) is the third leading cause of cancer death worldwide. Chronic infection by H.pylori and EBV is related to the multistep cascade of GC. This cascade hypothesizes that a specific sequence of lesions leads to GC. Epigenetic processes, such as DNA methylation or miRNAs, are new players in the pathogenesis of GC. We aim to identify novel upregulated microRNAs associated with the multistep cascade through the use of open access databases and bioinformatics tools. Methods: We selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One possible explanation is the small sample size, where there are only 12 Her2 subtypes. We similarly investigated the top 10 genes out of the 94 genes uniquely selected by pETM from 109 uniquely selected sites and found that 9 genes were reported to be associated with cancers: CLTC (P€ arssinen et al, 2007) and NSD1 (Stephens et al, 2009) were reported to be associated with breast cancer; SLC25A2 (Motamedian et al, 2015) and ESRRA (Micci et al, 2014) were reported to be associated with ovarian cancer; FSD1 (Yamashita et al, 2006) and CREB3L3 (Wichmann et al, 2015) were reported to be associated with gastric cancer; CARD14 (Oudes et al, 2005) was reported to be associated with prostate cancer; LRRFIP1 (Ariake et al, 2012) was reported to be associated with colorectal cancer; and PARD3 was reported to be associated with both esophageal squamous cell carcinoma (Zen et al, 2009) and lung squamous cell carcinomas (Bonastre et al, 2015).…”
Section: Real Data Applicationsmentioning
confidence: 99%
“…One possible explanation is the small sample size, where there are only 12 Her2 subtypes. We similarly investigated the top 10 genes out of the 94 genes uniquely selected by pETM from 109 uniquely selected sites and found that 9 genes were reported to be associated with cancers: CLTC (P€ arssinen et al, 2007) and NSD1 (Stephens et al, 2009) were reported to be associated with breast cancer; SLC25A2 (Motamedian et al, 2015) and ESRRA (Micci et al, 2014) were reported to be associated with ovarian cancer; FSD1 (Yamashita et al, 2006) and CREB3L3 (Wichmann et al, 2015) were reported to be associated with gastric cancer; CARD14 (Oudes et al, 2005) was reported to be associated with prostate cancer; LRRFIP1 (Ariake et al, 2012) was reported to be associated with colorectal cancer; and PARD3 was reported to be associated with both esophageal squamous cell carcinoma (Zen et al, 2009) and lung squamous cell carcinomas (Bonastre et al, 2015).…”
Section: Real Data Applicationsmentioning
confidence: 99%